Vasektomi sebagai Syarat Penerima Bantuan Sosial: Tinjauan Filosofis Hukum Kesehatan sebagai Hak Asasi Manusia - Sabrina Nuraini Sari; Suriyani Mansyur; Nella Septyani Suade; Sitti Nariman Korompot; Amelia Agustina; Yuyut Prayuti (Jurnal Hukum Lex Generalis, 2024)
This paper analyzes the proposed policy of requiring vasectomy as a condition for receiving social assistance in Bandung from the perspective of health law as a human right. Using a normative juridical and philosophical approach, this study demonstrates that such a policy contradicts the principles of bodily autonomy and freedom guaranteed under both national and international law. The recent revision of the Health Law, namely Law No. 17 of 2023, strengthens the position of the right to health as part of human rights, which demands that any health intervention be based on consent rather than coercion.